An empirical model for refrigerant flammability based on molecular structure and thermodynamics. (August 2019) - Linteris, Gregory T.; Bell, Ian H.; McLinden, Mark O.
Abstract: Screening methods for refrigerant blend flammability using metrics that can be easily calculated are of great interest to the refrigerant industry. Existing flammability metrics such as heat of combustion are not adequate for hydrofluorocarbon blends. Alternative metrics are needed that can be used to assess the flammability of refrigerant blends without requiring time-consuming experimental measurements. In this work, we study the combination of the maximum adiabatic flame temperature and the fluorine-substitution ratio as metrics for characterizing the flammability of refrigerant blends. The combination of these metrics yields an estimate of the flammability class of refrigerants (both blends and pure fluids) containing hydrofluorocarbon and hydrocarbon components. The calculations of adiabatic flame temperature are carried out with the open-source chemical kinetics software package Cantera using a mechanism available in the literature.